2009
DOI: 10.2174/138920209788920985
|View full text |Cite
|
Sign up to set email alerts
|

CENPA a Genomic Marker for Centromere Activity and Human Diseases

Abstract: Inheritance of genetic material requires that chromosomes segregate faithfully during cell division. Failure in this process can drive to aneuploidy phenomenon. Kinetochores are unique centromere macromolecular protein structures that attach chromosomes to the spindle for a proper movement and segregation. A unique type of nucleosomes of centromeric chromatin provides the base for kinetochore formation. A specific histone H3 variant, CENPA, replaces conventional histone H3 and together with centromere-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 111 publications
(162 reference statements)
0
26
0
Order By: Relevance
“…HJURP and CENPA interact for correctly loading new CENPA-containing nucleosomes on the centromere, thus ensuring fidelity during chromosome segregation [24,25]. Hu et al studied BCa cell lines and primary BCa cohorts and found that there was a statistically significant correlation between mRNA expression levels of HJURP and CENPA [27]. In vitro studies in BCa cell lines showed that RT led to increased apoptosis in cells with higher HJURP levels compared to cells with low HJURP expression levels; whereas using RNA interference studies (RNAi), it was shown that knocking down HJURP in human BCa cells led to decreased sensitivity to RT [26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HJURP and CENPA interact for correctly loading new CENPA-containing nucleosomes on the centromere, thus ensuring fidelity during chromosome segregation [24,25]. Hu et al studied BCa cell lines and primary BCa cohorts and found that there was a statistically significant correlation between mRNA expression levels of HJURP and CENPA [27]. In vitro studies in BCa cell lines showed that RT led to increased apoptosis in cells with higher HJURP levels compared to cells with low HJURP expression levels; whereas using RNA interference studies (RNAi), it was shown that knocking down HJURP in human BCa cells led to decreased sensitivity to RT [26].…”
Section: Resultsmentioning
confidence: 99%
“…Mis-localization of CENPA leading to genome instability has been suggested [27]. In colorectal cancer cells, CENPA over-expression has been shown to result in mistargeting of the protein to noncentromeric regions, thus depleting other centromere-kinetochore components and disrupting the kinetochore complex.…”
Section: Resultsmentioning
confidence: 99%
“…CENP-A is required for the recruitment of centromeric proteins, proper kinetochore assembly, and chromosome segregation. After DNA replication and cytokinesis, CENP-A accumulates in the nucleosome region of replicated centromeres to maintain homeostasis between CENP-A protein levels and the epigenetic mechanism of chromatin assembly of the newly replicated centromeres (32, 33). If there is a defect in the completion of cytokinesis, then CENP-A will not accumulate in the nucleosome region of the newly replicated centromeres and will accumulate in the cytosol as free CENP-A protein.…”
Section: Discussionmentioning
confidence: 99%
“…Human histone H3 has 6 different variants, among which CENP-A (CenH3, centromeric H3) is the most well known [51]. CENP-A plays a critical role to chromosome segregation via centromere association [42,52] – It replaces H3 at centromeres and is crucial to dictating centromeric positioning on chromosomes. The timing of CENP-A incorporation is critical as unscheduled CENP-A insertion disrupts kinetochore assembly and function [53].…”
Section: Architectural and Functional Components Of Chromatinmentioning
confidence: 99%